PERLINDUNGAN HUKUM TERHADAP PENJAMIN UNTUK MEMPEROLEH PEMBAYARAN KEMBALI DARI DEBITUR YANG WANPRESTASI JIKA PENJAMIN TELAH MELAKSANAKAN KEWAJIBANNYA PADA BANK BNI CABANG DENPASAR - Yasa, I Gede Krisna Adi; Atmadja, Ida Bagus Putra; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
This study aimed to describe the execution of the credit agreement with a guarantee. Particularly in the case of bail bonding and how the protection of the law against the guarantor in case the debtor defaults. This research is an empirical juridical is to study the behavior of the parties directly involved in the work activity of users kreditdengan deposit guarantees to third parties. This study was conducted at a branch of Bank BNI denpasar